2020 National Conference on Communications (NCC) 2020
DOI: 10.1109/ncc48643.2020.9056003
|View full text |Cite
|
Sign up to set email alerts
|

OTFS: Interleaved OFDM with Block CP

Abstract: Orthogonal time frequency space (OTFS) modulation is a recently proposed waveform for reliable communication in high-speed vehicular communication scenarios. It has better resilience to inter-carrier interference (ICI) than orthogonal frequency division multiplexing (OFDM). In this work, we describe OTFS as block-OFDM with a cyclic prefix and time interleaving. This interpretation helps one visualize OTFS in the light of OFDM as well as it also helps in analyzing the gain obtained by OTFS over OFDM. Further, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…y(k , L p +l ) = . Also, as explained in the [32], the time domain signal can be viewed as the interleaved OFDM, in which an N-point FFT is taken along the Doppler axis and then interleaved to get the time domain signal. If this is applied to the received delay-Doppler signal y(k , l ), then the signal without CP can be given as,…”
Section: Appendix a Proof Of Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…y(k , L p +l ) = . Also, as explained in the [32], the time domain signal can be viewed as the interleaved OFDM, in which an N-point FFT is taken along the Doppler axis and then interleaved to get the time domain signal. If this is applied to the received delay-Doppler signal y(k , l ), then the signal without CP can be given as,…”
Section: Appendix a Proof Of Theoremmentioning
confidence: 99%
“…Such modifications not only improve the immunity of OFDM to inter-carrier interference (ICI), which is caused by high Doppler in high mobility conditions and phase noise at high carrier frequencies, but also allow a smooth transition from 4G (IMT-Advanced [9]) to 5G with minimal changes. In a recent work by the authors [10], it VOLUME 4, 2016 i This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 License. For more information, see https://creativecommons.org/licenses/by-nc-nd/4.0/ This article has been accepted for publication in a future issue of this journal, but has not been fully edited.…”
Section: Introductionmentioning
confidence: 99%
“…The above channel diagonalization will enable a one-tap detector and equalizer in accordance with the pretty simple input-output relation, so (5) produces an ideal communication system.…”
Section: A Weyl-heisenberg Basismentioning
confidence: 99%
“…Because of the enormous advantage against Doppler spread, OTFS has attracted widespread attention as a next generation modulation scheme. To analyze the gain obtained by OTFS over OFDM, OTFS was described as block-OFDM with a cyclic prefix and time interleaving [5].…”
Section: Introductionmentioning
confidence: 99%
“…Such modifications not only improve the immunity of OFDM to inter-carrier interference (ICI) caused by high Doppler in high mobility conditions and phase noise at high carrier frequencies but also allow a smooth transition from 4G (IMT-Advanced [9]) to 5G with minimalistic changes in the system configuration. In a recent work by the authors [10], it is shown that orthogonal time frequency space (OTFS) [11]- [13] outperforms adaptive OFDM used in 5G-NR in such high ICI conditions.…”
Section: Introductionmentioning
confidence: 99%